The changing scenario of pattern of peripartum hysterectomy: prevention and preparedness matters - Rengaraj, Sasirekha; Rajamanickam, Saranya; Thiyagalingam, Sutharsika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Peripartum hysterectomy is a life-saving procedure, often associated with significant morbidity. The indication for peripartum hysterectomy has been shifted from PPH and rupture uterus to placental abnormalities and haemorrhage. Reducing the number of caesarean sections is the major step towards minimizing the chance of undergoing peripartum hysterectomy in subsequent pregnancy at the same time the morbidity is more if the peripartum hysterectomy is a on table decision. Methods: This was a descriptive study from a tertiary care centre, South India and all the case records of women who underwent peripartum hysterectomy were reviewed from 2012 to 2017. All the details including demographic details, clinical characteristics, indications and clinical outcome of those women were recorded. The data was analyzed using SPSS version 20. Results: The incidence of peripartum hysterectomy was 0.7/1000 deliveries and it was 0.24% and 0.03% after caesarean section and vaginal deliveries respectively. The placental abnormalities (46.2%) were the commonest cause followed by uterine atony (28.8%) and rupture uterus (21.2%). It was total hysterectomy in all of them except 2 women who underwent subtotal hysterectomy (3.8%) and the commonest visceral injury was bladder (15.4%). The maternal mortality rate was 9.8% and 61.5% (n=32) received massive blood transfusions. Conclusions: Even though a life-saving procedure, the timing and the preoperative hemodynamic status of the women were the major determinants of adverse outcome associated with peripartum hysterectomy. Preoperative planning and risk stratification models are essential to minimize the risk of undergoing hysterectomy and to reduce the morbidity associated with the procedure.